Design and Experiment of Obstacle Avoidance Mower in Orchard - Yi Yang; Yichuan He; Zhihui Tang; Hong Zhang (Agriculture)
In order to solve the problem of mowing between plants in Xinjiang trunk orchards, an obstacle avoidance mower suitable for trunk orchard planting mode was designed. The whole structure, working principle and main parameter design of the obstacle avoidance mower are introduced. The finite element analysis and kinematic analysis of the cutter are carried out on the premise of using a Y-shaped cutter and its arrangement, and the condition that the inter-row mower does not leak is determined. Through the modal analysis of the frame, the range of the first six natural frequencies of the frame is determined and compared with the frequency of the main excitation source of the machine to determine the rationality of the frame design. On the premise of simplifying the inter-plant obstacle avoidance mechanism into a two-dimensional model for kinematics analysis, the motion parameters of the key components of the machine were determined. At the same time, the virtual kinematics simulation single-factor test of the designed inter-plant obstacle avoidance device was carried out with the help of ADAMS 2020 software. Through the reduction in and calculation of the motion trajectory of the simulation test, it was finally determined that the forward speed of the machine, the elastic coefficient of the reset spring and the compression speed of the hydraulic cylinder were the main influencing factors of the inter-plant obstacle avoidance mower. The orthogonal test was designed and the optimal solution of the three test factors was determined. The optimal solution is taken for further field test verification. The results show that when the tractor forward speed is 1.5 km∙h−1, the hydraulic cylinder compression speed is 225 mm∙s−1, and the elastic coefficient of the reset spring is 29 N∙mm−1, the average leakage rate between the orchard plants is 7.64%, and the obstacle avoidance pass rate is 100%. The working stability is strong and meets the design requirements.